SYSTEMATIC LITERATURE REVIEW (SLR): PERAN CIRCULAR ECONOMY DALAM MENGURANGI LIMBAH INDUSTRI HALAL FASHION PERSPEKTIF MAQASHID SHARIAH - Mursilah, Pembayun; Ritonga, Iskandar; Mugiyati; Muhaimin, Hikmah (JURNAL ILMIAH EDUNOMIKA, 2025)
The rapid growth of the halal fashion industry raises concerns about the environment, particularly regarding textile waste, which contradicts the principles of sustainability in Islam. This study aims to analyze the role of the circular economy in waste reduction within the halal fashion industry from the perspective of Maqashid Syariah. Employing the Systematic Literature Review (SLR) method, this research examines previous studies focused on the application of the circular economy in the halal fashion sector. The findings indicate that circular economy principles, such as reuse, recycling, and extending product life, significantly contribute to waste reduction and align with Maqashid Syariah, particularly in preserving wealth (hifz al-mal) and the environment (hifz al-biah). The study concludes that integrating the circular economy with the principles of Islamic economics promotes a more sustainable and competitive halal fashion industry. A key implication of this research is the necessity for collaboration among policymakers, industry stakeholders, and consumers to establish regulations and practices that foster a sustainable halal fashion business ecosystem.